Elevation in tropical sky islands as the common driver in structuring genes and communities of freshwater organisms. Issue 1 (December 2017) - Gueuning, Morgan; Suchan, Tomasz; Rutschmann, Sereina; Gattolliat, Jean-Luc; Jamsari, Jamsari; Kamil, Al; Pitteloud, Camille; Buerki, Sven; Balke, Michael; Sartori, Michel; Alvarez, Nadir
Abstract Tropical mountains are usually characterized by a vertically-arranged sequence of ecological belts, which, in contrast to temperate habitats, have remained relatively stable in space across the Quaternary. Such long-lasting patterning of habitats makes them ideal to test the role of environmental pressure in driving ecological and evolutionary processes. Using Sumatran freshwater mayfly communities, we test whether elevation, rather than other spatial factors (i.e. volcanoes, watersheds) structures both species within communities and genes within species. Based on the analysis of 31 mayfly (Ephemeroptera) communities and restriction-site-associated-DNA sequencing in the four most ubiquitous species, we found elevation as the major spatial component structuring both species and genes in the landscape. In other words, similar elevations across different mountains or watersheds harbor more similar species and genes than different elevations within the same mountain or watershed. Tropical elevation gradients characterized by environmental conditions that are both steep and relatively stable seasonally and over geological time scales, are thus responsible for both ecological and genetic differentiation. Our results demonstrate howin situ ecological diversification at the micro-evolutionary level might fuel alpha- and beta- components of diversity in tropical sky islands.